2016
DOI: 10.1159/000447694
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Study for the Diagnosis of House Dust Mite Allergy - The Value of Recombinant Allergen-Based IgE Serology

Abstract: Background:Dermatophagoides pteronyssinus is one of the most important perennial allergen sources worldwide. Molecular diagnostics using the commercially available major allergens (Der p 1 and Der p 2) in combination with Der p 10 do not detect house dust mite (HDM) sensitization in a number of cases when used alone. The objective was to evaluate the IgE reactivity profiles of these patients using an experimental immunoassay biochip. Methods: Sera of HDM-allergic patients (positive skin prick test, CAP class ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 26 publications
2
41
0
1
Order By: Relevance
“…Efficient diagnostic guidelines leading to appropriate treatment are therefore urgently needed. Several studies have shown that allergen molecule-based diagnosis is more precise in identifying the sensitizing allergen sources [19,20,21,22,23] and that it is possible to select allergens for AIT more precisely according to component-resolved diagnosis with allergen molecules than based on diagnosis with allergen extracts [10,11]. However, to the best of our knowledge, our study is the first to investigate in a real-life setting whether allergen molecule-based testing is more cost-effective in selecting the correct AIT vaccines than conventional allergy diagnosis based on SPT with allergen extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient diagnostic guidelines leading to appropriate treatment are therefore urgently needed. Several studies have shown that allergen molecule-based diagnosis is more precise in identifying the sensitizing allergen sources [19,20,21,22,23] and that it is possible to select allergens for AIT more precisely according to component-resolved diagnosis with allergen molecules than based on diagnosis with allergen extracts [10,11]. However, to the best of our knowledge, our study is the first to investigate in a real-life setting whether allergen molecule-based testing is more cost-effective in selecting the correct AIT vaccines than conventional allergy diagnosis based on SPT with allergen extracts.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are registered in the allergen database (www.allergen.org) and summarized in Table 1. These developments were enabled by the application of recombinant DNA technology, which opened up new possibilities for the field of allergy, leading not only to the production of purified recombinant house dust mite allergens but also to the standardization of molecule-based preparations for diagnosis and allergen-specific immunotherapy [20]. Since the first data of a purified recombinant B. tropicalis allergen (rBlo t 5) published in 1995 by Arruda et al [21], several research groups have produced B. tropicalis allergens in recombinant form using different expression systems [12,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Information about a detailed allergenicity evaluation is currently available for only 10% of all IgE binding proteins in the databases. Completing this task will allow a better assessment of the pathogenic role of each mite allergen as has been recently suggested for Der p 23 [17,18] and could be great independently of its IgE-binding frequency [19][20][21]. Recognizing that regional combinations of mite allergens are more appropriate and less expensive than large panels of just IgE-binding components will also help.…”
Section: Mite Allergens and Precision Medicinementioning
confidence: 95%
“…There are a number of mite IgE-binding components available for CDR, including species-specific and cross-reacting molecules, most of them with well-defined structural and epitope data, although not all with empirically demonstrated allergenicity. A necessary step, the determination of the IgE reactivity against mite components in different populations and environments, has partially accomplished [16][17][18]. However, the analyses of these data have been based on the frequency of IgE reactivity, not including other aspects of allergenicity.…”
Section: Mite Allergens and Precision Medicinementioning
confidence: 99%